Surgical outcomes of women undergoing radical resection of deep endometriosis of the sacral plexus: A prospective cohort study - Gernot Hudelist; Ezgi Darici Kurt; Gábor Szabó; Dominika Miklos; Theresa Hudelist; Attila Bokor (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Surgical resection of sacral plexus endometriosis (SPE) is contemplated in severely symptomatic patients not responding to medical or hormonal therapy. However, there is only limited data on the effects of surgery on pain and neurological symptoms. This study aims to report on the surgical outcomes in terms of pain and neurological symptom reduction in women undergoing surgical resection of SPE. Material and Methods Thirty premenopausal patients with histologically confirmed SPE who underwent surgical resection of the disease between 2018 and 2024 were included in this multicenter prospective analysis. The primary outcome was the change in neurological symptoms reflected by sacral radiculopathy including dysaesthesia, paraesthesia, hyperaesthesia, and pain. The secondary outcome was post‐surgical morbidity reflected by rates of major intra‐ and postoperative complications. Results All patients exhibited DE affecting the sacral roots S1‐S4, whereas no case of isolated supracardinal sciatic nerve involvement was observed. Out of 30 patients, one was lost to follow‐up leaving 29 patients for final analysis. Six (20%) of the 30 patients underwent partial resection of the sacral root because of endometriotic infiltration of the nerval tissue. In all other patients, dissection and shaving with cold scissors were sufficient to remove DE affecting the sacral root. Dysaesthesia was observed in 13/30 (43.3%), paraesthesia in 16/30 (53.3%), hyperaesthesia in 5/30 (16.7%), and secondary motor dysfunction in 4/30 (13.3%), preoperatively. The mean follow‐up interval was 25.5 ± 20.2 months showing an overall improvement in sacral radiculopathy in 93.1% (27/29) of the patients. A significant decrease in numeric rating scale (NRS) scores of dysaesthesia (p = 0.003), paraesthesia (p ≤ 0.001) and hyperaesthesia (p = 0.068) were observed post‐surgically. Equally, reduced pain symptoms including dysmenorrhea, dyspareunia and dyschezia (all p ≤ 0.001) with a relevant increase in post‐surgical quality of life scores (p ≤ 0.001) were recorded. De novo hyperaesthesia and paraesthesia occurred in 6.8% (2/29) and 3.4% (1/29) of the patients, respectively. Major Clavien‐Dindo grade III complications occurred in 13.3% (4/30) of the cases. Conclusions Radical resection of symptomatic deep endometriosis affecting the sacral plexus reduces neurological and pain symptoms and leads to an increase in quality of life but is associated with high surgical morbidity.